An Efficient Approach of Peak to Average Power Ratio Reduction in OFDM Using CAP-PT Method - Raja Rajeshwari, C.; Rajkumari, M. (Asian Journal of Electrical Sciences, 2012)
An Orthogonal Frequency Division Multiplexing (OFDM) system has been proposed as a standard for the mobile communication systems. Despite the advantages of OFDM signals like high spectral efficiency and robustness against ISI, the OFDM signals have some disadvantages which the main one is the high peak to average power ratio (PAPR). The reason of high PAPR is that in the time domain, the OFDM signal is actually sum of many narrowband signals. At some time instances, the sum of these narrowband signals may be large and at the other time may be small, which means that the peak of the signal is much larger than the average value. This high PAPR signal when transmitted through a nonlinear power amplifier creates spectral broadening and also an increase in the dynamic range of the digital to analog converter (DAC). The result will be an increase in the cost of the system and reduction in efficiency. Hence, the technique to overcome this problem in OFDM systems is necessary. The existing method doesn’t have high capability of PAPR reduction with significant high Bit Error Rate (BER) degradation. Hence this proposed CAP-PT (Clipping, Amplification and Peak Windowing/ Partial Transmit) method combines the effect of clipping the peak signals and amplifies the signals that have low amplitude. Out of band radiations which is caused by clipping is suppressed by peak windowing process. Then followed by partial transmit which reduces in band distortions. The PAPR reduces to the great extent without BER degradation. Simulation results demonstrate that the proposed CAP-PT method yields the better performance than the existing methods.